2014
DOI: 10.3892/etm.2014.1524
|View full text |Cite
|
Sign up to set email alerts
|

Yanshu spraying agent, a traditional Chinese medicine, relieves chronic pharyngitis in animals by anti-inflammatory and antibacterial effects

Abstract: Chronic pharyngitis is chronic inflammation that is often caused by repeated occurrences of acute pharyngitis or upper respiratory tract infections, including Streptococcus and Staphylococcus. The present study aimed to investigate the effects of Yanshu spraying agent (Yanshu) in relieving chronic pharyngitis, as well as the possible underlying mechanisms. The results revealed that Yanshu inhibited chronic inflammation in ammonia-induced chronic pharyngitis in rabbits and cotton pellet-induced granuloma tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Although there are many antibiotics, glucocorticoids, and NSAIDs that can inhibit the exacerbation of pharyngitis, the side effects of these drugs can be significant to the point of intolerability over extended periods of use. At present, the treatment of CP with TCM is a popular and acceptable curative treatment [13,31,32]. TCM has relatively limited side-effects, does not adversely impact the microbiome, is inexpensive, and is thus a good candidate for long-term treatment, in comparison with antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many antibiotics, glucocorticoids, and NSAIDs that can inhibit the exacerbation of pharyngitis, the side effects of these drugs can be significant to the point of intolerability over extended periods of use. At present, the treatment of CP with TCM is a popular and acceptable curative treatment [13,31,32]. TCM has relatively limited side-effects, does not adversely impact the microbiome, is inexpensive, and is thus a good candidate for long-term treatment, in comparison with antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Pharyngitis. Patients with pharyngitis are mainly characterized by dryness of the pharyngeal cavity, foreign body sensation, itching sensation, irritating cough, and aching feeling and swelling in the throat [19]. TCM usually depends on the principle of "Shengjin Runzao Huatan" to relieve symptoms of patients with pharyngitis.…”
Section: Rstf Significantly Ameliorate the Symptoms Ofmentioning
confidence: 99%
“…The advanced bubble diagram is displayed in four dimensions: enriched content (pathway involved), enriched gene quantity, enrichment ratio (enrichment factor), and enriched salience. The principle of the bubble diagram is very simple; that is, according to the order of significance of enrichment from high to low, the first few pathways with the highest significance (generally [15][16][17][18][19][20] are selected, and the number of genes enriched is multidimensionally displayed. As shown in Figure 4(d), candidate targets could mainly be assigned to the defence response to the bacterium, immune response, NF-κB pathway, response to drug, and DNA damage response signalling pathways.…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
“…In China, acute pharyngitis is mainly treated with antiviral drugs, antibiotics or traditional Chinese medicine (TCM) [ 2 , 3 ]. TCM plays an increasingly important role in the treatment of chronic pharyngitis, for the etiology of chronic pharyngitis is complex, and many studies have shown that TCM shows significant effect on this disease [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%